2.2–2.7 μm side wall corrugated index coupled distributed feedback GaSb based laser diodes. (26th May 2015) - Gaimard, Q; Larrue, A; Triki, M; Adelin, B; Nguyen-Ba, T; Rouillard, Y; Gauthier-Lafaye, O; Teissier, R; Vicet, A
Abstract: We report on the modeling, growth, processing, characterization and integration in a gas detection setup of side wall corrugated distributed feed-back antimonide diode lasers emitting at 2.28 and 2.67 μ m. The laser structures were grown by molecular beam epitaxy on GaSb substrate. Ridge lasers were fabricated from the grown wafers according to the following process: a second order Bragg grating was defined on the sides of the ridges by interferometric lithography, optical lithography and etched in a Cl-based inductively coupled plasma reactor. The devices exhibit a power reaching 40 mW, a side mode suppression ratio better than 28 dB and a tuning range of 3 nm at room temperature. One of these devices was successfully integrated in a tunable diode laser absorption spectroscopy setup, thus demonstrating that they are suitable for gas analysis.